Mr Quiet - Hargreaves, Roger (World International Ltd, 1976)
Mr. Quiet, who lives in a small cottage in the middle of the woods in a country called Loudland, has a problem when he attempts to buy food but cannot be heard by the noisy inhabitants of the town.
Keywords: Juvenile literature-Fiction